Modeling of Steam Generation Process in the Supercritical Once-Though Boiler in the Thermal Power Plant - Nguyen, Dang Binh Thanh; Nguyen, Trung Dung; Ta, Hong Duc (JST: Engineering And Technology For Sustainable Development, 2022)
The paper establishes a simple and practical model for a water-wall system comprising supercritical once-through boilers. The mathematical model of the system is developed and built based on mass, energy and momentum balance equations. The System of equations gives the linear and differential algebraic equations expressed by pressure and temperature. The model is solved by a program written in the MATLAB application. The data in the literature are also provided for comparison, and good agreement with the model results. The MATLAB program could be applied for basic design of process in the supercritical once though boiler in the thermal power plants in Vietnam.